Job Satisfaction Of Nurses In Hospital Kota Bharu, Kelantan - Ong, Soon Chuan (2002)

(untitled)
The nursing section plays a very important role in assisting patients seeking for health services in the hospital. A nurse who has a high job satisfaction will strive to provide the best to her patients. In view of this fact, a survey was carried out to assess the relationship between job satisfaction and the quality of work. This study also took into consideration other factors which also contributed to job satisfaction such as interest in nursing itself, sense of pride in the profession, opportunities for further studies and promotion, place of work, working environment, self-confidence, team spirit, amount of workload, attitude of the superiors as well as the subordinates, patients' demands, arrangement of the duty roster, family support incentives and so on. This survey was carried out on 340 nurses in the Kota Bharu Hospital.